KEMAMPUAN BERPIKIR REFLEKTIF PESERTA DIDIK MELALUI MODEL COOPERATIVE LEARNING TIPE STAD BERBANTUAN MIND MAPPING - Aliya Monika Br Ginting; Saleh Haji; Hari Sumardi (LPPM Universitas Bina Bangsa, 2023)
The purpose of this study was to find out how the STAD Cooperative Learning and Mind Mapping models helped 8th graders at SMP Negeri 11 Bengkulu City improve their reflective thinking skills. The design in this study used The-Nonequivalent Pretest-Posttest Control Group Design. This research is a quasi-experimental research. The total population in this study were 198 people and were all eighth grade students at SMP Negeri 11 Bengkulu City. The sample of this study consisted of 23 students of class VIII G and 19 students of class VIII H. Each sample class held three meetings during the study. The research data shows that the average value of n-gain in the experimental class is 69.21% which is quite effective, and the total value ranges from 33.23% to 82.61% which is classified as good (A). A value is obtained from learning outcomes using the t-test. (2-tailed) = 0.046 < significant level = 0.05 so that the STAD type cooperative learning model assisted by Mind Mapping is said to be able to improve reflective thinking skills in class VIII students at SMP Negeri 11 Kota Bengkulu